Detection of luxS Gene in Serratia marcescens and rpoS Gene in Enterobacter cloacae Isolates Using PCR Reaction - Muhammed, Naba'a A; Farhan, Muthana B; Shabeeb, Zeyad A (Al-Nahrain Journal of Science, 2018)
luxS and rpoS genes were involved in the regulation of some biological processes, which interfere with virulence of Serratia marcescens and Enterobacter cloacae bacterial species sequentially. luxS have an important activity in Quorum Sensing (QS) processes, but rpoS interfere with tolerance and resistance processes toward stress conditions correlating with its virulence. The study aimed to detect rpoS presence in E. cloacae and luxS gene presence in S. marcescens separately isolated from 16 leukaemia patients (4 of S. marcescens and 12 of E. cloacae), who characterised with bacteraemia by using primers designed for this purpose by using PCR technique. The results showed that all of the bacterial isolates of S. marcescens contain luxS gene, while no one of E. cloacae isolates show positive results for rpoS gene. The study concluded that S. marcescens has high virulence as a result of luxS presence, which controls Quorum sensing and prodigiosin formation and affecting host immunity. Moreover, the negative results of rpoS gene can be explained according to two possibilities: the gene can be found in the isolates with a copy differ from the registered sequences of the rpoS gene, or the gene did not present in those isolates with presence of alternatives offset its activities